Uteroplacental fibrinolysis in normal pregnancy, preeclampsia and intrauterine growth retardation - O'Reilly, Ian E. G. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Obstetrics and Gynaecology, 2000)
Normal pregnancy is accompanied by extensive changes in the coagulation and fibrinolytic systems. Within the uteroplacental vasculature decidual spiral arteries undergo extensive morphological changes to allow for increased blood flow to the placenta. These changes include fibrin deposition in the placenta and placental bed. Cytotrophoblasts have been found in proximity to these fibrin deposits. In pre-edam psia (PET) and intrauterine growth retardation (lUGR) increased deposits of fibrin are found in the placenta and placental bed. Poor implantation into the placental bed by trophoblast cells is associated with PET and lUGR.
Keywords: Obstetrics, Ph.D.; Ph.D. Trinity College Dublin